Efficacy and safety of acupuncture for IgA vasculitis abdominal pain: protocol for a systematic review and meta-analysis - Xiangge Ren; Peidong Zhao; Wen-Sheng Zhai (BMJ Open)
Introduction Abdominal pain is one of the most common symptoms in patients with IgA vasculitis (IgAV), adversely affecting both physical and mental health. Clinical studies have demonstrated that acupuncture can quickly alleviate pain and reduce the duration of abdominal pain episodes. Given its growing acceptance in clinical practice, acupuncture is increasingly being adopted for managing IgAV-related abdominal pain. The objective of this systematic review is to evaluate and synthesise evidence regarding the efficacy and safety of acupuncture for IgAV abdominal pain.Methods and analysis Eight databases will be systematically searched from their inception to 1 June 2025: China National Knowledge Infrastructure, Chinese Biomedical Literature Database (China Biology Medicine), VIP Database, Wanfang Database, PubMed, Embase, Cochrane Library and Web of Science. Only randomised controlled trials investigating acupuncture for IgAV abdominal pain, published in Chinese or English, will be included. Two independent researchers will perform study selection, data extraction and risk-of-bias assessment. The primary outcomes include symptom and sign scores and time to abdominal pain resolution. Secondary outcomes comprise recurrence rate, incidence of adverse events and urinalysis results. Risk of bias will be evaluated using the Cochrane Risk of Bias Tool (V.2.0). Meta-analyses will be conducted using Review Manager software (V.5.3). For continuous data, we will calculate standardised mean differences with 95% CIs. For dichotomous outcomes, relative risks and 95% CIs will be calculated. Subgroup analyses will be performed where feasible. The overall evidence quality will be graded using the Grading of Recommendations Assessment, Development, and Evaluation approach.Ethics and dissemination Ethical approval is not required for this study as it does not involve the collection of primary patient data. The results of this meta-analysis will be disseminated through peer-reviewed publications.PROSPERO registration number CRD42023483770